The unified theory of acceptance and use of technology (UTAUT): a literature review - Williams, Michael D; Rana, Nripendra P; Dwivedi, Yogesh K (Journal of enterprise information management, 2015)
Purpose – The purpose of this paper is to perform a systematic review of articles that have used the unified theory of acceptance and use of technology (UTAUT). Design/methodology/approach – The results produced in this research are based on the literature analysis of 174 existing articles on the UTAUT model. This has been performed by collecting data including demographic details, methodological details, limitations, and significance of relationships between the constructs from the available articles based on the UTAUT. Findings – The findings indicated that general purpose systems and specialized business systems were examined in the majority of the articles using the UTAUT. The analysis also indicated that cross-sectional approach, survey methods, and structural equation modelling analysis techniques were the most explored research methodologies whereas SPSS was found to be the largely used analysis tools. Moreover, the weight analysis of independent variables indicates that variables such as performance expectancy and behavioural intention qualified for the best predictor category. Moreover, the analysis also suggested that single subject or biased sample as the most explored limitation across all studies. Research limitations/implications – The search activities were centered on occurrences of keywords to avoid tracing a large number of publications where these keywords might have been used as casual words in the main text. However, we acknowledge that there may be a number of studies, which lack keywords in the title, but still focus upon UTAUT in some form. Originality/value – This is the first research of its type which has extensively examined the literature on the UTAUT and provided the researchers with the accumulative knowledge about the model.